Pengaruh Penerapan Mobile Banking Terhadap Pertumbuhan Aset dan DPK Pada PT. Bank DKI - Agus Wismo Widodo (Tekinfo: Jurnal Bidang Teknik Industri dan Teknik Informatika, 2021)
The research objective was to determine the optimization of the application of Mobile Banking at PT. Bank DKI. The process of collecting data uses library data and field data by means of observation, interviews, and documentation. The results showed that the application of Mobile Banking service greatly influenced the collection of third party funds. The supporting factor in the application of Mobile Banking is the prevalence of people using smart phones, both among business and social circles, which is marked by the ownership of a smart phone in almost all circles, whether professionals, employees and students. With the use off smart phone in almost all circles, Mobile Banking facilities are increasingly wide open to become a potential market wherever they are. Inhibiting factors is the lack of socialization and education to the public related to the features, it is hoped that Bank DKI can Icrease Asset and third party funds increase market share, expand service access to the public and be able to compete with conventional banks. Keywords: Mobile Banking, Current account, Saving account, Deposit,Asset